Analisis Jumlah Angka Kuman Pada Spons Dapur - Awalia Gusti; Lindawati Lindawati; Aidil Onasis; Rahmi Hidayanti (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Food utensil doesnot hygiene cause disease transmission. Food utensil can be free form microorganisms through the washing process. Washing utensil using software and hardware, such as water and detergent, while hardware such us basin, faucet, sinks and sponge. A habitually leave sponges in the washing water resulting in growing microorganism. Porous spongy materials can be a major source of contamination, because corss contamination transmits pathogenic microbe origating from spoiled food residues in food scarps. This study aims to determine the number of germs on kitchen sponges used to wash cutlery. This research is descriptive, examining the number of germs on sponges based on the frequency of use and storage. The sample criteria are sponges used by households after use are washed and dried, after use are washed and dried adm sponge after use are not washed and not dried. Sample were taken and grown on agar media, then incubated in incubator. The research was conducted in the laboratory of Department of Environmental Healt. The result, the number of germ on kitchen sponges were different based on the treatment. The kitchen sponge are washed and dried after used have lower germ numbers than kitchen sponges that are not washed and not dired after used. The recommended, kitchen sponges after use should be washed and dried to stop the growth of bacteria and change the sponges once a week.